2012
DOI: 10.1016/j.jcat.2012.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation of benzene and toluene over size controlled Pt/SBA-15 catalysts: Elucidation of the Pt particle size effect on reaction kinetics

Abstract: . (2012) 'Hydrogenation of benzene and toluene over size controlled Pt/SBA-15 catalysts : elucidation of the Pt particle size eect on reaction kinetics.', Journal of catalysis., 292 . pp. 64-72. Further information on publisher's website:http://dx.doi.org/10.1016/j.jcat.2012.04.022Publisher's copyright statement: This is the author's version of a work that was accepted for publication in Journal of Catalysis. Changes resulting from the publishing process, such as peer review, editing, corrections, structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 125 publications
(65 citation statements)
references
References 64 publications
3
61
0
1
Order By: Relevance
“…Most of the attention has been paid to obtain supported catalysts based on size-controlled NPs in a range of size considered of special interest for catalysis, usually under 10 nm, to assess structure-sensitiveness [36,[38][39][40]. Nevertheless, size-controlled synthesis of catalyst with ranges of NP sizes beyond 10 nm are less studied, in spite of some authors have reported higher activity at the top of their ranges of size studied (%10 nm) [38,41].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the attention has been paid to obtain supported catalysts based on size-controlled NPs in a range of size considered of special interest for catalysis, usually under 10 nm, to assess structure-sensitiveness [36,[38][39][40]. Nevertheless, size-controlled synthesis of catalyst with ranges of NP sizes beyond 10 nm are less studied, in spite of some authors have reported higher activity at the top of their ranges of size studied (%10 nm) [38,41].…”
Section: Introductionmentioning
confidence: 99%
“…We also observed fourfold change in turnover rates between nanoparticles of platinum in the 2-to 4-nm range and in the 4-to 6-nm range. The size and shape dependence of nanoparticles can readily be controlled by colloid science technology (36,38,39) (Fig. 1C).…”
Section: Metal Nanoparticles For Size-dependent Covalent Bond Catalysismentioning
confidence: 99%
“…SBA-15 is a mesoporous amorphous silica that has been commonly used as a support for various catalysts. 32,33 It has hexagonally aligned channel-like pores with average pore diameter of 6.4 nm as characterized by TEM and N 2 physisorption. MCF-17 is another amorphous silica with interconnected spherical pores with average diameter of 26.5 nm.…”
Section: Effect Of Catalyst Microstructure and Density Of Acid Sitesmentioning
confidence: 99%